2018
DOI: 10.2340/00015555-2863
|View full text |Cite
|
Sign up to set email alerts
|

The Position of Targeted Next-generation Sequencing in Epidermolysis Bullosa Diagnosis

Abstract: The precise classification of epidermolysis bullosa (EB) into 4 main types and more than 30 subtypes is based on the level of skin cleavage, as well as clinical and molecular features, and is crucial for early prognostication, case management, genetic counselling and prenatal or pre-implantation diagnosis. We report here the molecular pathology of 40 consecutive cases of suspected EB, which were investigated by immunofluorescence mapping (IFM) and/or by a targeted next-generation sequencing (NGS) multi-gene pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 18 publications
2
28
0
4
Order By: Relevance
“…Vahidnezhad et al developed a multigene panel including 21 genes and found an efficiency of 83.5% predicting the subtype of EB in 76 out of 91 families . Has et al elucidated 90% (36 of 40) of the studied cases by a NGS‐panel that included 49 genes . Finally, Lucky et al found an efficiency of 97.7% (42/43 patients) in an NGS assay that included 21 genes, in which all the identified mutations were present in only five genes ( KRT5 , KRT14 , LAMB3 , COL17A1 , COL7A1 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Vahidnezhad et al developed a multigene panel including 21 genes and found an efficiency of 83.5% predicting the subtype of EB in 76 out of 91 families . Has et al elucidated 90% (36 of 40) of the studied cases by a NGS‐panel that included 49 genes . Finally, Lucky et al found an efficiency of 97.7% (42/43 patients) in an NGS assay that included 21 genes, in which all the identified mutations were present in only five genes ( KRT5 , KRT14 , LAMB3 , COL17A1 , COL7A1 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Using an EB multigene panel, we have recently identified an additional unrelated patient. He had mild skin fragility and was a compound heterozygote for c.46C>T and a mutation leading to a premature termination codon …”
Section: New Eb Clinical Phenotypesmentioning
confidence: 75%
“…For research purposes, other candidate genes can be added if they are functionally related or suspected to be potential functional modifiers. Based on our recent experience, we have designed a panel containing 20 EB‐associated genes and 29 supplementary candidate genes. With this approach, we achieved a 90% detection rate for the disease‐causing variants.…”
Section: New Diagnostic Methodsmentioning
confidence: 97%
See 2 more Smart Citations